THEMATIC GROUPS OF GEOGRAPHICAL TERMS - Khabibulloyeva Gulchekhra Komiljonovna (Bright Mind Publishing, 2025)
In this article, several geographical terms and their thematic groups are given. These geographical terms are used in our life every day. The importance of these terms are great, because they do not only used in geography, but also in other fields, too. Sometimes, people can confuse, while they are classifying them, it is better to translate in L1 first, and after catching the meaning it will be easier to classify. In this work, author presented the terms and explained their usage.
Keywords: Geography, mountains, refer, concept, comparison, groups, learn, formation, countries.